An Agent Approach to Spatial Information Grid Architecture Design - Luo, Yingwei; Wang, Xiaolin; Xu, Zhuoqun (Computing and Informatics, 2012)
Spatial information grid (SIG) is a spatial information infrastructure that has the capability of providing services on-demand. SIG is a distributed network environment, which links spatial data resources, computing resources, storage resources, software, tools and users. SIG can integrate massive distributed heterogeneous spatial information resources, provides uniform management and process, and, furthermore, coordinate different resources to complete large-scale and complex spatial tasks and applications. In this paper, agent technology is adopted to construct a SIG framework, which contains three layers: users/applications layer, agent services layer and information layer. Different applications can get their spatial information via agent services, and agent services make the procedure of navigating and accessing spatial information transparent to users. Also, the implementation issues of the framework are discussed in detail, including Geo-Agents, an agent-based distributed GIS system, spatial information management, collaboration and parallel mechanism, load control strategy, and a sample.